Anti-tumor Activity of Plantago lanceolata Aqueous Extract In Vitro and Genotoxicity by Micronucleus Assay In Vivo - Al-Mosawie, Eman Ali H.; Al-Maliky, Worood K. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The study is designed to evaluate the effect of the aqueous extract of the P. lanceolata plant, as well as to know the effect of the drug CCl4 on the formation of micronucleus in vivo 48 female albino mice. In the study mice were separated into eight groups treated intraperitoneally for seven day first group Negative control, second positive control( CCl4 0.02%), third group aqueous extract (250 mg/kg), fourth group  aqueous extract (500 mg/kg), fifth group (CCl4 0.02%) plus aqueous extract (250 mg/kg), sixth group (CCl4 0.02%) plus aqueous extract (500 mg/kg), seventh group aqueous extract (250 mg/kg) plus (CCl4 0.02%), and eighth group aqueous extract (500 mg/kg) plus (CCl4 0.02%). The genetic-cellular aspect involved measuring the coefficient of micronucleus formation in bone marrow cells in mice treated with CCl4 and plant aqueous extract. The results showed that the treatment of mice with the drug led to a rise in the coefficient of micronucleus formation compared to the negative control group. In addition, it showed the plant's ability to reduce the drug CCl4 effect in the totals of overlaps between the plant extract and the drug at the concentrations used for the plant 250 and 500 μg/ml and reduce the formation of micronucleus.The cellular toxicity of the plant’s aqueous extract on the liver cancer cell line was assessed in HepG2 (liver cancer cell line) and the WRL68 (hepatic human cell line) using concentrations (25, 50, 100, 200, and 400 μg /ml) from the plant’s aqueous extract on the HepG2 liver cancer cell line. The results showed a decrease in cell viability depending on aqueous extract concentration. The vitality of cancer cells decreased with the increase in concentration; the viability of the aqueous extract of the plant on cancer cells reached the minimum at concentration 400 μg/ml 45.34±4.44, while it reached the maximum when concentration  25 μg/ml 84.53±2.41.